Piracy in the Indian film industry : Copyright and cultural consonance - Arul George Scaria (Cambridge University Press, 2014)
"Provides insights into the copyright law by analysing the social, cultural, historical, legal, and economic dimensions of copyright piracy in the Indian film industry"--